Characterizing the Portuguese Blogosphere - Couto, Telmo; Ribeiro, Cristina; Nunes, Sérgio (Proceedings of the International AAAI Conference on Web and Social Media, 2009)
Over the years, blogs have become a popular and influent part of the web, having many distinctive features - they are usually thematic and organized by communities, and their contents have a chronological order. In this paper, we present a characterization of the portuguese blogosphere based on a large set of portuguese blogs collected from multiple sources across a 5-year period. The extent of our collection allows us to draw some conclusions on the evolution of the blogging activity over the years. We survey and apply methods that have been used for web and blog characterization and, using samples of blogs obtained from other sources, we try to estimate the extent to which this collection can be representative of the portuguese blogosphere. The paper presents multiple statistics that allow us to characterize the portuguese blogosphere and compare it to results obtained with other studies.